Efficacy of Hypnosis in Adults Undergoing Surgical Procedures: A meta-analytic update. (April 2021) - Holler, Mareike; Koranyi, Susan; Strauss, Bernhard; Rosendahl, Jenny
Abstract: In this meta-analysis we updated a review from 2013 investigating the evidence on the efficacy of hypnosis in adults undergoing surgical procedures compared to standard care alone or an attention control. A comprehensive literature search using Medline, CENTRAL, Web of Science, PsycINFO, ProQuest Dissertations and Theses database, and manual searches were conducted to identify randomized controlled trials. In this update, N  = 23 eligible studies were added to the existing study pool, resulting in N  = 50 studies with 4269 patients. Random effects meta-analyses revealed positive treatment effects on mental distress ( g  = 0.55, 95% CI [0.39; 0.70], NNT  = 3.32), pain ( g  = 0.37, 95% CI [0.25; 0.50], NNT  = 4.78), medication consumption ( g  = 0.46, 95% CI [0.23; 0.68], NNT  = 3.95), recovery ( g  = 0.26, 95% CI [0.09; 0.42], NNT  = 6.91), and surgical procedure time ( g  = 0.23, 95% CI [0.14; 0.33], NNT  = 7.6). No effects were found for physiological parameters ( g  = 0.13, 95% CI [−0.06; 0.33], NNT  = 13.26). 95% prediction intervals included the null effect for all outcomes except for procedure time. In conclusion, although positive effects of hypnosis could be shown, overall generalizability is limited due to high heterogeneity of the study results that could not be explained by characteristics of patients, interventions, or study methods. Highlights: This meta-analysis summarizes the evidence on the efficacy of hypnosis in surgical patients. The evidence of a previous review was updated by adding 23 new studies. Benefits of hypnosis on various surgically relevant outcomes are demonstrated. Effects do not differ based on characteristics of patients, intervention or control group.